NAFKAH ANAK PASCA PERCERAIAN: STUDI KASUS DI PENGADILAN AGAMA SUKOHARJO - Nadhila Tsabita Fathurrahman; Heri Hartanto (Sebelas Maret University, 2025)
This article examines the judge's considerations in determining child support in divorce cases at the Religious Court of Sukoharjo. The purpose of this article is to examine the regulations of child support post-divorce in Indonesia, as well as the considerations for determining child support rights, with a focus on ensuring justice for the child and the party obligated to provide support. The research revealed that there are no special regulations regarding the determination of child support after divorce, even though the regulations mandate that parents still bear the cost of maintaining the child. Consequently, this leads to differences in the judge's considerations on determining the amount of child support in each divorce decision, which could result in injustice for the parties involved. Therefore, particular variables are needed to determine child support, such as by referring to other similar laws and regulations, like minimum wage calculation formula contained in Article 88C and Article 88D of Law No. 6 of 2023 concerning the Stipulation of Perpu No. 2 of 2022 concerning Job Creation into Law, which is according to economic and employment conditions, considers the variables of economic growth, inflation, and certain indexes.